Dynamics Simulation and Modeling of Double Circular Arc Spiral Bevel Gear based on UG and ADAMS - Zhang Yufeng; Wu Baolin (Jixie chuandong)
Based on tooth surface equation of double circular arc spiral bevel gear,using the three- dimensional modeling software of UG,the three- dimensional parametric modeling of double circular arc spiral bevel gear and the virtual assembling of the active gear and the driven gear in the UG is realized. The gear data is converted into parasolid format and introduced into the ADAMS,the variation of angular velocity and meshing force of the active gear and the driven gear are analyzed. Through the simulation analysis,it is verified to be reasonable of double circular arc spiral bevel gear parametric modeling,and a reference for the improvement and optimization of gear transmission design,geometric and strength calculation is provided.